Global mean sea level likely higher than present during the holocene - Roger C. Creel; Jacqueline Austermann; Robert E. Kopp; Nicole S. Khan; Torsten Albrecht; Jonathan Kingslake (Nature Communications)
Abstract Global mean sea-level (GMSL) change can shed light on how the Earth system responds to warming. Glaciological evidence indicates that Earth’s ice sheets retreated inland of early industrial (1850 CE) extents during the Holocene (11.7-0 ka), yet previous work suggests that Holocene GMSL never surpassed early industrial levels. We merge sea-level data with a glacial isostatic adjustment model ensemble and reconstructions of postglacial thermosteric sea-level and mountain glacier evolution to estimate Holocene GMSL and ice volume. We show it is likely (probability P = 0.75) GMSL exceeded early industrial levels after 7.5ka, reaching 0.24 m (−3.3 to 1.0 m, 90% credible interval) above present by 3.2ka; Antarctica was likely (P = 0.78) smaller than present after 7ka; GMSL rise by 2150 will very likely (P = 0.9) be the fastest in the last 5000 years; and by 2060, GMSL will as likely than not (P = 0.5) be the highest in 115,000 years.